THE INFORMATIONAL SAFETY MODEL OF A TONIC (ENERGY) DRINK WITH - Kotova T.V.; Solopova A.N.; Poznyakovskiy V.M. (Техника и технология пищевых производств, 2015)
The article presents the results of the study in determining the safety of tonic (energy) drinks with the help of three-factor regressionanalysis using a mathematical model of quality. The study has been performed on adult Wistar rats of both sexes in accordance with the requirements to the content and the humane treatment of experimental animals. The animals consumed the water solution of Schizandra chinensis extract at the rate of 4 mcg per 100 g of the body weight.The purpose of the study is to assess the risk of toxic or side effects when consuming the drink with Schizandra chinensis basing on the results obtained during pre-clinical trials with animal models using a mathematical model of changes of lactate dehydrogenase(LDH) activity in quantitative indices of the activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinekinase (CK).The risk of damage to the cell membranes has been estimated by the quantitative content of the glycolytic enzymeLDH, the activity of which increases above the reference values of 170-480 U/l when having toxic damages of cells and tissues ofheart, kidney, liver and brain. The regression equations have been obtained which describe the change in LDH activity depending on X1 - ALT, X2 - AST, X3 - CK with laboratory animals of both sexes taking a drink with Schizandra chinensis . The significance of all coefficients of the regression equations has been shown, since their values are between the lower and upper limits of the confidence interval. The possibility of using the change in LDH activity in laboratory animals taking a drink with Schizandra chinensis as biomarkers of damage to the cell membranes has been theoretically proved. There has been LDH decrease within the normal range in laboratory animals, indicating the biological safety of the beverage to the human body.